Penerapan Model Cooperative Learning dengan Media Montessori dalam Meningkatkan Hasil Belajar Materi Siklus Hidup Hewan Siswa Kelas III di SDN Margmulyo 1 Ngawi - Kiki Kristiya Ana; Nur Syamsiyah; Budi Utomo (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
The objective of this research is to enhance the academic performance of Grade III students at SDN Margomulyo 1 Ngawi in the subject of animal life cycle by implementing a cooperative learning approach using Montessori media. The study methodology used is classroom action research (CAR) consisting of two cycles. During the first phase, the assessment of student learning outcomes revealed a limited level of proficiency, as just 44% of students successfully attained the desired learning goals. Following the implementation of the cooperative learning paradigm using Montessori media in the second cycle, there was a notable improvement, with 88% of students attaining mastery and an average score rise of 82%. This research provides evidence that the collaborative learning approach, along with Montessori media, is successful in improving students' comprehension and academic achievements in the subject of animal life cycles.